Passive tools for enhancing muscle-driven motion and locomotion - Minetti, A. E. (The Journal of Experimental Biology, 2004)
Musculo-skeletal systems and body design in general have evolved to move effectively and travel in specific environments. Humans have always aspired to reach higher power movement and to locomote safely and fast, even through unfamiliar media (air, water, snow, ice). For the last few millennia, human ingenuity has led to the invention of a variety of passive tools that help to compensate for the limitations in their body design. This Commentary discusses many of those tools, ranging from halteres used by athletes in ancient Greece, to bows, skis, fins, skates and bicycles, which are characterised by not supplying any additional mechanical energy, thus retaining the use of muscular force alone. The energy cascade from metabolic fuel to final movement is described, with particular emphasis on the steps where some energy saving and/or power enhancement is viable. Swimming is used to illustrate the efficiency breakdown in complex locomotion, and the advantage of using fins. A novel graphical representation of world records in different types of terrestrial and aquatic locomotion is presented, which together with a suggested method for estimating their metabolic cost (energy per unit distance), will illustrate the success of the tools used.